MODEL DISKUSI SASTRA DI KELAS 5 SEKOLAH DASAR (Studi Pengembangan Pembelajaran Sastra di Sekolah Dasar Negeri Cirebon) - Abdul Rozak (Program Studi Pendidikan Bahasa Indonesia Pascasarjana UGJ, 2012)
The writer considers the opportunities given by curriculum, the teachers’ potential to conduct literature learning well, the students’ potential as reader that could be developed and be given opportunities to explore he texts, and he potential of literature itself which is multi-interpreted. Based on those considerations, the writer integrates those opportunities and potential into a model of literature discussion.Based on the data analysis, the writer finds that: 1) the students get literature competence after they carry out activities that occupy them with literature. 2) The students could create events based on the text they read. 3) The students’ creativity is shown when they dramatize the events. 4) This model involves the four language skills. 5) The students use their knowledge on literature they get when they response. 6) Discussion on literature at elementary schools takes place in the form of question and answer.